Regression of gestational diabetes induced cardiomegaly in offspring of diabetic rat - Menezes,Honório Sampaio (2009)
PURPOSE: To compare body weight and length, heart weight and length, heart-to-body weight ratio, glycemia, and morphometric cellular data of offspring of diabetic rats (ODR) and of normal rats (control). METHODS: Diabetes was induced in 3 pregnant Wistar rats, bearing 30 rats, on the 11th day after conception by intraperitoneal injection of 50 mg/kg of streptozotocin. Six normal pregnant Wistar rats, bearing 50 rats, made up the control group. Morphometric data were obtained using a scale for the weight, length, heart and body measurements. Morphometric cellular data were obtained by a computer assisted method applied to the measurements of myocytes. Statistical analysis utilized Student's t-test, ANOVA and Levene test. RESULTS: Control offspring had greater mean body weight and length than offspring of diabetic rats (p < 0.001). Heart weight and length and heart-to-body ratios of newborn rats differed between groups at birth (p < 0.001), but showed no difference at 21 days. Mean nuclei area and perimetric value of the myocytes decrees throughout the first 21 days of life (p < 0.01) in the diabetic group. CONCLUSIONS: Heart hypertrophy on the offspring of diabetic rats at birth was demonstrated by the significant difference between the groups. After the eleventh day, no difference was found, which confirmed regression of cardiomegaly. The significant difference between the first and the 21th day of life, for nuclei area feature, demonstrate regression of cardiac hypertrophy in the offspring of diabetic rats.